Multiplicity of Positive and Nodal Solutions for Nonhomogeneous Elliptic Problems in Unbounded Cylinder Domains. (9th June 2009) - Hsu, Tsing-San
Abstract : We show that ifa ( x ) andf ( x ) satisfy some suitable conditions, then the Dirichlet problem− Δ u + u = a ( x ) | u | p − 2 u + f ( x ) inΩ has a solution that changes sign inΩ, in addition to two positive solutions whereΩ is an unbounded cylinder domain inℝ N .